2011
DOI: 10.1051/kmae/2011029
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation in the prevalence of the crayfish plague pathogen,Aphanomyces astaci, in three Czech spiny-cheek crayfish populations

Abstract: Key-words:Orconectes limosus, oomycete, infection prevalence, molecular detection, crayfish plagueNorth American crayfish species are natural hosts of the crayfish plague pathogen Aphanomyces astaci. The spiny-cheek crayfish Orconectes limosus, widespread in Central Europe, is the main reservoir of A. astaci in Czech Republic. We tested if there are temporal changes in the prevalence of infected individuals (i.e., the proportion of individuals in which the pathogen is detected) in spiny-cheek crayfish populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Selection of a suitable source of crayfish for parasite isolation was based on data of its prevalence in Czech populations of O. limosus . We chose a pond in Smečno (Central Bohemia, 50°11.3 0 N, 14°02.8 0 E), as the vast majority (ca 95%) of individuals sampled repeatedly from this locality were found to be infected by A. astaci (Matasová et al, 2011). Furthermore, the infection dose in some local crayfish individuals was high (up to agent level A5 after Vrålstad et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Selection of a suitable source of crayfish for parasite isolation was based on data of its prevalence in Czech populations of O. limosus . We chose a pond in Smečno (Central Bohemia, 50°11.3 0 N, 14°02.8 0 E), as the vast majority (ca 95%) of individuals sampled repeatedly from this locality were found to be infected by A. astaci (Matasová et al, 2011). Furthermore, the infection dose in some local crayfish individuals was high (up to agent level A5 after Vrålstad et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…The lower prevalence limit for an obligate crayfish parasite like A. astaci remains unknown. It has been shown that the pathogen prevalence in a weakly infected population decreases from April to November, whereas the prevalence in a highly infected population remains high over several years and during different seasons (Matasová et al, 2011).…”
Section: Pathogen Prevalencementioning
confidence: 99%
“…This, together with the catastrophic decline of native European crayfish (Bohman, Nordwall & Edsman, 2006;Holdich et al, 2009) suggests that the stable coexistence of American and European crayfish species is unlikely. Indications of pathogen-free American crayfish populations have also been found sporadically (Matasová et al, 2011;Skov et al, 2011). Indications of pathogen-free American crayfish populations have also been found sporadically (Matasová et al, 2011;Skov et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Providing conclusive evidence that some populations of potential A. astaci hosts (North American invasive crayfish) are likely to be uninfected requires much more intensive sampling effort [49]. Temporal fluctuations of the pathogen prevalence (or detectability) could also influence our results, as was shown for a Czech Orconectes limosus population studied over several seasons [54]. Thus, low A. astaci prevalence detected in some French signal crayfish populations does not mean that those pose a lower threat than other more infected populations of the same species.…”
Section: Discussionmentioning
confidence: 86%